Polygamy Mentoring in Indonesia: Al-Qur’an, Hadith and Dominant Discourse Resistance - Miski, Miski; Aulia, Mila; Jannah, Roudlotul; Laily, Ridya Nur (Universitas Islam Negeri (UIN) Salatiga, 2022)
This article intends to examine the phenomenon of polygamy mentoring in Indonesia, which is campaigned by Kiai Hafidin on the Robbanian Family Youtube account. This study focuses on how the interpretation of polygamy according to Kiai Hafidin, its correlation with polygamy that developed in Indonesia, and the religious problems in this country. The approach used is a virtual ethnographic approach (netnography) by applying two analytical models, discourse analysis and hermeneutical analysis. This research shows that the polygamy discourse delivered by Kiai Hafidin is allegedly based on the theological reasoning of QS. al-Nisa’ (4): 3 and 129, and the practice of polygamy by the Prophet Muhammad and his companions, but tends to be apologetic. Moreover, Kiai Hafidin’s polygamy discourse is positioned as resistance to the existing discourse in Indonesia, namely monogamy discourse. For Kiai Hafidin, polygamy is related to marriage and as an alternative to various socio-religious problems; for example, as a solution to the rise of adultery cases, many women are still single, and the depletion of religiously good women. However, apart from this, Kiai Hafidin’s polygamy discourse basically strengthens the interests of patriarchy, which further distances the ideal bond between men and women.